The behavior of the Bacillus probiotic species under conditions of co-cultivation - Knysh, O. V.; Martynov, A. V.; Pokhyl, S. I.; Skliar, N. I. (Сучасні медичні технологіЈі, 2023)
Combining probiotic bacteria is a promising strategy to increase the effectiveness and avoid side effects of probiotic therapy. Bacteria that find themselves in a common environment are able to both change their properties and show new ones under the influence of each other. The change of colonization and antagonistic properties, which provide bacteria with competitive advantages in the development of new spaces, deserves special attention. The aim of this research was to study the features of the mutual influence of probiotic bacilli: B. clausii, B. coagulans and B. subtilis on growth, swimming and swarming motility when co-cultivated on agar media of different solidity. Materials and methods. The study used commercial strains of bacilli from three probiotic preparations: Enterogermina, Lactovit forte and Subalin. The ability of the studied species of bacilli to influence each other’s growth was investigated by the agar block method (using 1.5 % nutrient agar) and the spot-on-lawn assay (using 0.7 % nutrient agar). The study of the mutual influence on swimming and swarming activity was carried out when bacilli were cultivated on 0.25 % and 0.70 % tryptone agar, respectively. The diameters of swimming halos and migration swarms formed by monoand mixed cultures were measured, and the areas covered by them were compared. The phenotypes of the meeting of swarms formed by cultures spotted on the swarm plates at different locations were also investigated. Results. The studied probiotic species of the bacilli did not show a strong ability to inhibit each other’s growth. The B. clausii culture had no inhibitory effect, and the B. coagulans culture demonstrated a moderate inhibitory influence on the growth of the other two species of bacilli when using both diffusion methods. The B. subtilis culture showed moderate or weak inhibitory activity against the B. clausii culture and weak or no inhibitory activity against the B. coagulans culture using the agar block method or spot-on-lawn assay, respectively. The B. coagulans + B. subtilis, B. clausii + B. coagulans and B. clausii + B. subtilis mixed cultures showed moderate, weak and no inhibitory activity against third cultures, respectively. The studied species of bacilli showed different swimming ability and swarming potential as well as the ability to influence each other’s motility. Swimming halos formed by the B. clausii + B. subtilis and B. clausii + B. сoagulans + B. subtilis mixed cultures covered significantly larger plate areas than the swimming halos formed by each culture separately during the same cultivation time. The highest swarming potential was observed in B. coagulans culture and B. cla usii + B. coagulans + B. subtilis mixed culture. The studied bacilli did not show the ability to merge swarms, but, on the contrary, their swarms at the point of contact formed visible “boundary” or “intermediate” lines, demonstrating the ability to identify nonself. Conclusions. The obtained results indicate the ability of the probiotic species of bacilli: B. clausii, B. coagulans and B. subtilis to mutually influence growth, swimming and swarm motility. The highest indicators of swimming and swarming of the triple mixed culture indicate an increase in the colonization potential of the studied bacilli when they are combined. The hypothesis of mutual induction of inhibitory compounds production by bacilli, which may increase the overall antagonistic potential of the triple mixed culture, is subject to further confirmation.